Analisis Pemahaman Konsep Besaran Mistar Satuan Melalui Bahan Ajar Multimedia Interaktif Siswa Kelas IV SDN 101869 Desa Sena - Pangadilan Daulay; Gustyven Tambunan; Rafiqi Hafidz Al Abrori; Gaberia Sitompul; Kenza Amanda Sihotang; Tesalonika Sinaga; Suyit Ratno (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This research aims to analyze and develop students' science process skills, particularly in the use of measuring instruments, and their influence on understanding the concepts of quantities and units in physics. This research is motivated by the importance of mastering skills in using measuring instruments in physics learning, as well as the need for innovative teaching materials to improve students' understanding of fundamental concepts. This study employs a mixed-methods approach, combining both quantitative and qualitative methods. The quantitative approach is used to analyze data on students' skills in using measuring instruments and their understanding of concepts through tests. Meanwhile, the qualitative approach is employed to analyze data from observations and interviews with students and teachers regarding the effectiveness of using guided inquiry-based interactive multimedia teaching materials. The interactive multimedia teaching materials developed in this research are designed to facilitate learning about measuring instruments and measurement using a guided inquiry approach. A behavioristic approach is also considered in the development of these teaching materials to ensure students receive appropriate reinforcement throughout the learning process. Through this research, it is hoped that effective ways to develop students' science process skills and enhance their understanding of measuring instruments and measurement concepts in physics will be discovered, ultimately improving physics learning outcomes as a whole.